A Microfluidic-Based Cell-Stretching Culture Device That Allows for Easy Preparation of Slides for Observation with High-Magnification Objective Lenses - Momoko Kato; Kae Sato (Micromachines)
Microfluidic-based cell-stretching devices are vital for studying the molecular pathways involved in cellular responses to mechanobiological processes. Accurate evaluation of these responses requires detailed observation of cells cultured in this cell-stretching device. This study aimed to develop a method for preparing microscope slides to enable high-magnification imaging of cells in these devices. The key innovation is creating a peelable bond between the cell culture membrane and the upper channel, allowing for easy removal of the upper layer and precise cutting of the membrane for high-magnification microscopy. Using the fabricated device, OP9 cells (15,000 cells/channel) were stretched, and the effects of focal adhesion proteins and the intracellular distribution of YAP1 were examined under a fluorescence microscope with 100× and 60× objectives. Stretch stimulation increased integrinβ1 expression and promoted integrin–vinculin complex formation by approximately 1.4-fold in OP9 cells. Furthermore, YAP1 nuclear localization was significantly enhanced (approximately 1.3-fold) during stretching. This method offers a valuable tool for researchers using microfluidic-based cell-stretching devices. The advancement of imaging techniques in microdevice research is expected to further drive progress in mechanobiology research.